The chalk man : a novel - Tudor, C.J (Crown Publishers, 2018)
"Narrated by 'Eddie' who receives a chalk drawing of a stick figure that hurtles him back to an innocent childhood game 30 years before which went terribly, terribly wrong. As history begins to repeat itself, it seems the game was never really over" --